2004
DOI: 10.1038/nn1351
|View full text |Cite
|
Sign up to set email alerts
|

Selective reconfiguration of layer 4 visual cortical circuitry by visual deprivation

Abstract: Visual deprivation during a developmental sensitive period markedly alters visual cortical response properties, but the changes in intracortical circuitry that underlie these effects are poorly understood. Here we use a slice preparation of rat primary visual cortex to show that 2 d of prior visual deprivation early in life increases the excitability of layer 4 circuitry. Slice recordings showed that spontaneous activity of layer 4 star pyramidal neurons increased 25-fold after 2 d of visual deprivation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
432
6
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(467 citation statements)
references
References 50 publications
28
432
6
1
Order By: Relevance
“…In terms of layer-specific gene expression, we unexpectedly found layer 2/3 to be enriched in pathways and genes involved in cytoskeletal assembly, calcium signaling pathway, MAPK signaling pathway, and long-term potentiation, which suggest that these neurons may be capable of high levels of synaptic plasticity. This result stands in contrast to previous reports indicating that layer 4 is particularly privileged in terms of plasticity (22,23). We found also that layer 5 is enriched for such terms as intermediate filament bundle assembly and regulation of exocytosis, which may be related to the fact that it contains projection neurons that are generally larger and have long-range axons projecting to subcortical targets, necessitating increased production of axonal proteins.…”
Section: Discussioncontrasting
confidence: 99%
“…In terms of layer-specific gene expression, we unexpectedly found layer 2/3 to be enriched in pathways and genes involved in cytoskeletal assembly, calcium signaling pathway, MAPK signaling pathway, and long-term potentiation, which suggest that these neurons may be capable of high levels of synaptic plasticity. This result stands in contrast to previous reports indicating that layer 4 is particularly privileged in terms of plasticity (22,23). We found also that layer 5 is enriched for such terms as intermediate filament bundle assembly and regulation of exocytosis, which may be related to the fact that it contains projection neurons that are generally larger and have long-range axons projecting to subcortical targets, necessitating increased production of axonal proteins.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, VGLUT2 may play such a role in cholinergic motoneurons via a recurrent collateral pathway onto Renshaw inhibitory neurons . Recurrent pyramidal neuron excitatory terminals display differential targeting to subclasses of GABA neurons in the cerebral cortex (DeFelipe, 2002;Melchitzky and Lewis, 2003;Maffei et al, 2004), some of which may provide powerful feedback inhibition onto pyramidal neurons (Reyes et al, 1998;Gupta et al, 2000;McBain and Fisahn, 2001;Markram et al, 2004;Turrigiano and Nelson, 2004). It has been shown in an individual neocortical pyramidal neuron that a 48 h treatment with BIC results in a reduction in quantal amplitude at its cortico-excitatory synapse (feedforward) and an increase in quantal amplitude at its cortico-GABAergic synapse (feedback), which may be attributable, in part, to postsynaptic changes (Rutherford et al, 1997Turrigiano et al, 1998).…”
Section: Scaling Of Vesicular Glutamate and Gaba Transporter Expressionmentioning
confidence: 99%
“…This idea is supported by findings that ODP is enhanced either by increasing GABAergic neurotransmission before the critical period (4) or by reducing GABA signaling after the critical period (5)(6)(7)(8). It has been suggested that, during the critical period, MD itself alters the balance of excitation and feedback inhibition within the visual cortex by depressing the activity of fast-spiking (FS) interneurons (9,10). In support of this idea, ODP is first detectable in the extragranular cortical layers [i.e., 2/3, 5, and 6 (11)], where depression of FS interneuron activity has been reported after brief MD.…”
mentioning
confidence: 92%